Kapasitas Guru Sebagai Fasilitator Dalam Membangun Pengetahuan Anak Usia Dini - Reviani, Monika Fitria (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Early childhood knowledge has a very important role in their development and growth. The teacher has an important role as a facilitator in building early childhood knowledge. This study aims to conduct a literature review on the teacher's role in helping children acquire relevant knowledge. This study uses a qualitative approach involving an analysis of literature from various sources related to early childhood knowledge and the role of the teacher. The results of this literature review reveal several important aspects of the teacher's role as a facilitator in building children's knowledge. Teachers have the ability to facilitate a learning environment that supports children's knowledge. By providing hands-on experience, teachers can encourage children to observe, experiment, and solve problems, thereby enriching their knowledge. Teachers also play a role in designing and implementing a curriculum that fits the needs and interests of children. With a child-centred approach. Through effective communication, teachers can build emotional bonds with children in solving problems together, and learning from each other between children. The role of the teacher as a facilitator in building early childhood knowledge is very important. Through hands-on experience, child-centred teaching, and positive social interactions, teachers can assist children in acquiring relevant and meaningful knowledge. The results of this literature review provide a solid foundation for the development of effective early education practices and reinforce understanding of the teacher's key role in shaping early childhood knowledge.